Games in Junior High School Mathematics Learning: Sematic Literature Rivew - Kusumayoni, Ni Made Sri Utami; Sariyasa; I Gusti Putu , Suharta (Program Studi Pendidikan Matematika Universitas PGRI Kanjuruhan Malang, 2026)
Mathematics learning at the junior high school (SMP) level requires an approach that is able to bridge abstract concepts with students' learning experiences. One such approach is the use of games. Therefore, this study aims to systematically examine the form, innovation, research variables, methodological approaches, roles, and advantages and disadvantages of games in mathematics learning. The method used is Systematic Literature Review (SLR) with a qualitative descriptive approach, based on the PRISMA 2020 protocol. Data sources are obtained from relevant scientific articles published in Indonesian or English between 2016 and 2025. The results of the study showed that the games applied were very varied, namely: educational games, quiziz, matrig, multimedia, android-based, character-based math games, snake and ladder games, interactive word wall-based, web-based games, monopoly, unomath, online games, and ludo. In conclusion, games in mathematics learning have the potential to foster independent and meaningful learning and can be an alternative learning strategy that is adaptive to current developments, for example games: education, quiziz, matrig, multimedia, android-based, character-based, snake and ladder games, interactive word wall-based, web, monopoly, unomath, online games, and ludo. It is suggested that further research can design games to make learning more innovative.